2019
DOI: 10.1002/cite.201800101
|View full text |Cite
|
Sign up to set email alerts
|

Flow Fields in Stirred Vessels Depending on Different Internal Heat Exchangers and Vessel Bottoms

Abstract: This study provides the influence of different heat exchanger internals (helical pipe coils, heating plugs, pipe registers) and reactor bottom shapes (torispherical/dished (Kloepper-shape), hemispherical, and flat) on the flow field, the turbulent kinetic energy, and the ratio of tangential flow in stirred vessels, based on extensive stereo PIV measurement series in refractive index-matched, optically completely accessible systems. The investigations impressively show advantages and disadvantages of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In follow-up investigations, a variation of the baffle number will be carried out in order to be able to evaluate whether adjustments for multistage systems need to be made and to eventually extend the measurement range into the fully turbulent state above Re R = 10 000 without unwanted vortex formation or surface gassing. Further experiments will focus on effects of different reactor bottom shapes and internals, as previous research [18,19] has proven that single-stage impellers are not sufficient in many such cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In follow-up investigations, a variation of the baffle number will be carried out in order to be able to evaluate whether adjustments for multistage systems need to be made and to eventually extend the measurement range into the fully turbulent state above Re R = 10 000 without unwanted vortex formation or surface gassing. Further experiments will focus on effects of different reactor bottom shapes and internals, as previous research [18,19] has proven that single-stage impellers are not sufficient in many such cases.…”
Section: Discussionmentioning
confidence: 99%
“…During the reference single-stage experiments, impellers were installed at a bottom clearance of h = D/3, following previous investigations [18,19,41,42], with the Reynolds number as the primarily varied parameter. For the multistage experiments, the installation heights of the impellers were varied in addition to that.…”
Section: Methodsmentioning
confidence: 99%
“…Nguyen et al [ 20 ] reported achieving an increase of 22% in the system COP by increasing the heat absorption of the medium in the ground using an IHX with the CO 2 direct expansion ground source heat pump (DX‐GSHP). Jaehrling et al [ 21 ] explored the advantages and disadvantages of IHX with different structures by analyzing the differences in the heat transfer and flow between the refrigerants. Kang et al [ 22 ] embedded an IHX into an HTHPS system with single‐stage compression, and concluded that the system COP increased with decreasing steam temperature as well as with increasing mass flow of water and refrigerant in the evaporator.…”
Section: Structural Characteristics Of Frs‐hthps and Rrs‐hthpsmentioning
confidence: 99%
“…As the flow and mixing ratios, however, depend on many parameters, such as stirrer type, rotation frequency, stirrer and reactor geometry, internals, and so forth, it is questionable whether different, unsystematically set stirring rates are the correct comparison variable, for instance, to transfer findings from inhibitor screenings in a stirred autoclave to the flow conditions in a pipeline [87].…”
Section: Introductionmentioning
confidence: 99%